2021
DOI: 10.1111/ajd.13703
|View full text |Cite
|
Sign up to set email alerts
|

Moisturisers from birth in at‐risk infants of atopic dermatitis – a pragmatic randomised controlled trial

Abstract: Background: Atopic dermatitis (AD) is a common, chronic dermatosis, with onset of disease often manifesting in early infancy. Past studies evaluating the early use of moisturisers in the prevention of AD had mixed results. Objectives:To compare the incidence of moderate or severe AD and total incidence of AD in a cohort of 'at-risk' infants treated with moisturisers from the first 2 weeks of life, to a similar group without moisturisers. Methods:We performed a single-centre, prospective, parallel-group, random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 22 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…Six studies 17,21–25 reported the incidence of adverse events (AEs) after interventions (Table 2). We did not perform data synthesis due to variations in categories, such as skin infections, slippages and irritant contact dermatitis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies 17,21–25 reported the incidence of adverse events (AEs) after interventions (Table 2). We did not perform data synthesis due to variations in categories, such as skin infections, slippages and irritant contact dermatitis.…”
Section: Resultsmentioning
confidence: 99%
“…We retrieved 802 relevant studies from the initial literature search and only 10 RCTs 12,[17][18][19][20][21][22][23][24][25] were determined to meet our selection criteria after screening the titles, abstracts and full texts. Moreover, we also identified one eligible study 26 from a previous meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations